Evidence for revision of the evaluated half-life of 207Bi. (April 2018) - Pibida, L.; King, L.
Abstract: The National Institute of Standards and Technology (NIST) compared the measured full-energy peak efficiency obtained from a large set of sources to that of a 207 Bi source obtained using three different half-life values. The values of the half-life used for this comparison are published in the Decay Data Evaluation Project (32.9 ± 1.4) years and the Evaluated Nuclear Structure Data File (31.55 ± 0.04) years, and in a recent NIST publication (31.20 ± 0.05) years (or (11395 ± 18) days). Highlights: Differences in 207 Bi half-life values. High purity germanium (HPGe) detectors for gamma-ray spectrometry measurements. Comparison of HPGe efficiency measurements using 207 Bi half-life published values.